Proceedings of the 20th ACM International Conference on Intelligent Virtual Agents 2020
DOI: 10.1145/3383652.3423917
|View full text |Cite
|
Sign up to set email alerts
|

Influence of virtual agent politeness behaviors on how users join small conversational groups

Abstract: Figure 1: A participant's view of the small group scenario as they approach. The agent shown on the left in each case invites the participant to join the group by conducting verbal and non-verbal behaviors related to the following politeness strategies, from left to right: (a) not face-threatening act (NOT); (b) indirect (IND); (c) negative (NEG); (d) positive (POS); (e) direct (DIR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In a study assuming a chat between a virtual agent and a person, it was reported that while the agent's use of PPS can reduce the impression of machine-ness (have no intention), the overall impression is higher with NPS [11]. In a study of multiparty conversations, in a task in which virtual agents conducting a multiparty conversation invite a user to join the conversation, the probability of the user joining the conversation was significantly increased when the agents used PPS [12]. Although these findings are useful for designing smooth interactions between people and agents, they are not necessarily applicable to other situations, as both studies were conducted for specific situations.…”
Section: Politeness Research On Agentsmentioning
confidence: 99%
“…In a study assuming a chat between a virtual agent and a person, it was reported that while the agent's use of PPS can reduce the impression of machine-ness (have no intention), the overall impression is higher with NPS [11]. In a study of multiparty conversations, in a task in which virtual agents conducting a multiparty conversation invite a user to join the conversation, the probability of the user joining the conversation was significantly increased when the agents used PPS [12]. Although these findings are useful for designing smooth interactions between people and agents, they are not necessarily applicable to other situations, as both studies were conducted for specific situations.…”
Section: Politeness Research On Agentsmentioning
confidence: 99%
“…We selected the rude and gentle vitality forms as being able to communicate and understand the related attitudes is particularly important for creation of successful humanartificial agent interaction. For instance, while previous studies show the important role of politeness in such interactions (see e.g., [6], [7], [8]), modelling politeness is often limited to verbal communication only. Being able by an artificial agent to detect and communicate gentle attitude with nonverbal behavior may be used to reduce social distance, increase affinity and trustfulness.…”
Section: Introductionmentioning
confidence: 99%